Produção de antígenos virais para detecção de anticorpos contra o vírus da cinomose canina - Magda Regina (1998)
Antigens of canine distemper virus (CDV) were prepared from chicken embryo tibroblast (CEP) or green monkey kidney cells (VERO). CDV infected monolayers and used to develope an indirect ELISA (iELlSA) for testing CDV specitic serum antibodies in dogs. 81 and 60 sera were assayed against CEF CDV antigen or VERO CDV antigen, respectively, all previously tested by serum neutralization (SN). Alternatives for producing iELlSA CDV antigen are dismissed in perspective of obtaining improved antigen yield as well as a higher specihcity and sensitivity.